Physics of Turbulent Jet Ignition Mechanisms and Dynamics of Ultra-lean Combustion - Biswas, Sayan (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book focuses on developing strategies for ultra-lean combustion of natural gas and hydrogen, and contributes to the research on extending the lean flammability limit of hydrogen and air using a hot supersonic jet. The author addresses experimental methods, data analysis techniques, and results throughout each chapter and: Explains the fundamental mechanisms behind turbulent hot jet ignition using non-dimensional analysis Explores ignition characteristics by impinging hot jet and multiple jets in relation to better controllability and lean combustion Explores how different instability modes interact with the acoustic modes of the combustion chamber. This book provides a potential answer to some of the issues that arise from lean engine operation, such as poor ignition, engine misfire, cycle-to-cycle variability, combustion instability, reduction in efficiency, and an increase in unburned hydrocarbon emissions. This thesis was submitted to and approved by Purdue University.